Gehörte Geschichten Phänomene des Auditiven - Lehnert, Nils; Schenker, Ina; Wicke, Andreas (De Gruyter, 2022)
Auditive texts are on the rise: audio plays, readings, podcasts, audioguides, and electroacoustic experiments reveal the diversity of audible stories. The contributions in this volume systematize the genres of this diverse range of objects and model theoretical and methodological approaches that they apply in the analysis of media-specific examples. Semiotic approaches are accompanied by cultural studies perspectives.